การจำกัดวาระการดำรงตำแหน่งของสมาชิกสภาผู้แทนราษฎรในประเทศไทย - พิมลกร แปงฟู (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This thesis studies on the relationship and influence of term limits on the House of Representatives in Thailand. The thesis methodology analyzes comparative between term limits on the House of Representatives under western democratic political culture, such as United Kingdom, United State of America and term limits on the House of Representatives under Thai political culture, which influence from authoritarian political culture, Thai feudalism, charismatic authority and patronage system.According to the study, it appears that Thai political culture under authoritarian political culture, Thai feudalism, charismatic authority and patronage system, which are deep-seated in Thai society for a long time, affected on the political system electoral system, parliamentary system and Thai political behavior in patron-client association. Even if many constitution as the model for making the draft constitution, but the old Thai patronage system still appears in rural Thai society, Thai bureaucracy, electoral behavior and legislative behavior in Thailand. So, Thai political culture which does not accord with democracy and comply with western democratic political culture, non-term limits on the House of Representatives under constitution, affected to the internal structure of political system and was making long periods of one-party domination of legislatures. Then non-term limits as one way of accumulation of excessive power, corruption and tyrannical rule by exercise of the power under patronage system. Therefore, constitution should be amended by writing term limits on the House of Representatives, as one way for rotate in office and bring the must professional skill politicians, generate new blood and women into legislative branch for promotion of public interest under universal democracy.